Profesionalisme Guru Sekolah Minggu: Kunci Meningkatkan Kepatuhan Pelayanan - Napitupulu, Basariah; Nugroho, Andreas Eko; Sianipar, Rikardo Panusunan (STTI Harvest Semarang, 2025)
Sunday School ministry is an important part of the church that aims to shape Christian children by instilling Biblical values and building their faith from an early age. The success of this ministry is greatly influenced by the level of compliance of Sunday School teachers in carrying out their duties. One way to improve compliance is through enhancing the professionalism of Sunday School teachers, which includes competence in teaching, responsibility, and commitment to ministry. This study uses a literature analysis method to examine the relationship between Sunday School teachers' professionalism and ministry compliance. Based on a study of various theological literature, Christian education, and church ministry management. The results of the study concluded that the professionalism of Sunday School teachers has a significant impact on compliance in Sunday School ministry. Factors such as training, spiritual guidance, and church support play a key role in improving the quality of Sunday School ministry. Therefore, the church needs to develop strategic policies to strengthen the professionalism of Sunday School teachers for the sake of the sustainability of effective and quality Sunday School ministry. AbstrakPelayanan Sekolah Minggu adalah bagian penting dalam gereja yang bertujuan untuk membentuk anak-anak Kristen dengan menanamkan nilai-nilai Alkitab dan membangun iman mereka sejak dini. Keberhasilan pelayanan ini sangat dipengaruhi oleh tingkat kepatuhan guru Sekolah Minggu dalam menjalankan tugasnya. Salah satu cara untuk meningkatkan kepatuhan adalah melalui peningkatan profesionalisme guru Sekolah Minggu, yang mencakup kompetensi dalam mengajar, tanggung jawab, dan komitmen terhadap pelayanan. Penelitian ini menggunakan metode analisis literatur untuk menelaah profesionalisme guru Sekolah Minggu dan kepatuhan dalam pelayanan. Berdasarkan studi terhadap berbagai literatur teologi pendidikan Kristen, dan manajemen pelayanan gerejawi. Hasil penelitian menyimpulkan bahwa profesionalisme guru Sekolah Minggu memiliki dampak signifikan terhadap kepatuhan dalam pelayanan Sekolah Minggu. Faktor seperti pelatihan, pembinaan spiritual, dan dukungan gereja memainkan peran kunci dalam meningkatkan kualitas pelayanan Sekolah Minggu. Oleh karena itu, gereja perlu mengembangkan kebijakan strategis untuk memperkuat profesionalisme guru Sekolah Minggu demi keberlangsungan pelayanan Sekolah Minggu yang efektif dan berkualitas.